(untitled) (Al-Academy, 2026)
In light of political hegemony and unequal power relations, an opposition to discrimination between classes in society emerged, which criticized social and authoritarian structures, and addressed the fundamental social and political issues in weak societies, where violence, discrimination and marginalization prevailed, and from there it became an introduction to the study of marginalized societies and ethnic groups. On this basis, the research consists of four chapters: The first chapter included the research problem, which ended with the question of how critical ethnography as a critical and aesthetic value represented by Djako Kasi Natali ceramics contributed to contemporary ceramic art), its importance, goal, and definition of its terminology, while the second chapter included three axes, the first. Ethography (its concept and origins), and the second is conceptual approaches to critical ethnography. The third is ethnography and its representations in fine art.Through the theoretical framework’s indicators, the research moved to the third chapter, which included its procedures, where the research community consisted of (15) works; their samples were intentionally selected and amounted to (3). After that, and based on the analysis of the samples, the research moved to the fourth chapter. It included the results, their discussion, and conclusions. The most important results reached by the research are the following : 1- Symbolic work in sample models is the ethnographic basis that reveals class differentiation in its aesthetic form, as in sample models. 2- The contemporary ceramic aesthetic formation is based on the discourse of the aesthetic image of the African marginalized, and this is consistent with all sample models. 3- Critical reading appeared in temporal transformations represented by the main pressure that helped transform the marginalized into a center on the social and human levels that the potter embodied in her works.